The Role of Accounting Information Systems as Mediating the Effect of Business Strategy on MSME Performance (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
This study aims to examine the role of accounting information systems (AIS) as a mediating variable in the relationship between business strategy, specifically differentiation strategy, and the performance of Micro, Small, and Medium Enterprises (MSMEs). This study was conducted in Surakarta using a questionnaire survey method of 122 MSME actors from various types of businesses. The results of the analysis using PLS-SEM show that business strategy has a significant positive effect on MSME performance both directly and through the mediation of AIS, business strategy has a positive effect on AIS and AIS have a positive effect on performance. It has been demonstrated that AIS plays a significant role in assisting business strategy to attain a competitive edge and improved performance. This research provides practical implications for MSMEs to optimize business strategy and AIS implementation as a management tool that supports competitiveness as well as recommendations for policy makers to support the adoption of information technology in the MSME sector. The findings also extend the literature on the relationship between business strategy, AIS, and MSME performance, especially in the context of developing countries.